Root (GUM) and its derivatives between Lexical Sematics and Semantics Koranic (Journal of the College of Education for Women, 2019)
As the word can fluctuate between central and peripheral dlalten it represents the first lexical meaning and the second represents the meaning that gain by the context in which it appear so this research came to show signs that can be acquired the root ( GUM ) and its derivatives from the contexts in which it is mentioned in the Koran as well as siqnificant Lexical if this research is divided on two first is eating Lexical semantics , the second handled connotations in the Koran was based on what the commentators and concemed with the meanings of the Koran and the owners Almagamat in astatement that the semantic .